2019
DOI: 10.1111/ijsa.12256
|View full text |Cite
|
Sign up to set email alerts
|

Organizational commitment and job performance: Examining the moderating roles of occupational commitment and transformational leadership

Abstract: To address why the relationship between affective organizational commitment and job performance varies, we draw on the theorization of Meyer, Becker, and Vandenberghe to propose moderation of affective occupational commitment and transformational leadership, separately and interactively. Data collected from 398 employees and their supervisors supported our hypotheses. Specifically, affective organizational commitment was more strongly associated with job performance for employees with high occupational commitm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 52 publications
7
47
0
5
Order By: Relevance
“…This study also found that effective commitment plays a vital role as mediators in GCG and KM effect on professional performance. This evidence in line with studies concluded that GCG influences affective commitment [56] [57], KM influences affective commitment [58]- [61], and affective commitment affects professional performance [47]- [55]. This finding reveals empirical facts that the existence of affective commitment is very important to be considered in the context of increasing professional performance through GCG and KM.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This study also found that effective commitment plays a vital role as mediators in GCG and KM effect on professional performance. This evidence in line with studies concluded that GCG influences affective commitment [56] [57], KM influences affective commitment [58]- [61], and affective commitment affects professional performance [47]- [55]. This finding reveals empirical facts that the existence of affective commitment is very important to be considered in the context of increasing professional performance through GCG and KM.…”
Section: Discussionsupporting
confidence: 88%
“…It implies to increase professional performance reflected in teaching skills, communication skills, personality authority, social skills, technical competence, and emotional stability. The studies carried out by research approve that GCG affects affective commitment [56] [57], while the other studies conducted scholars concluded that affective commitment affects professional performance [47]- [55]. Based on argues and studies above, the sixth hypothesis in this study is: H 6 : GCG had an indirect effect on professional performance mediating by affective commitment.…”
Section: Gcg and Professional Performance Mediating By Affective Commmentioning
confidence: 75%
See 1 more Smart Citation
“…Organizational Commitment is of significant research interests because of the relationship between commitment and desirable organizational outcomes such as creativity and innovativeness (Ali. & Puah, 2017;Battistelli, Odoardi, Vandenberghe, Di Napoli, & Piccione, 2019;Li & Zheng, 2014) increased job performance (Kim et al, 2018;Sungu et al, 2019) employee loyalty (Suresh & Mahalingam, 2018) and job satisfaction (Sait, 2017;Luz, Paula, & Oliveira, 2018). Committed employees help create an organization"s competitive advantage and are motivated to give their best to the organization.…”
Section: Organizational Commitment (Oc) and Job Performance (Jp)mentioning
confidence: 99%
“…If a leader is not able to motivate followers, then the daily operations will start to unbind, and the organization can disintegrate. Sungu (2019) and Zeinab (2019) both published articles analyzing organizational commitment and job performance. The results from Sungu (2019) showed that employees had better job performance and higher occupational commitment when 10 there was a transformational leadership approach displayed by their supervisors.…”
Section: Traits Of Leadershipmentioning
confidence: 99%